Les paroles de pierre - mots et monogrammes – de quelques chancels paléochrétiens - Chevalier, Pascale (ASPICE HUNC OPUS MIRUM: Festschrift on the occasion of Nikola Jakšić's 70th birthday, 2020)
The Early medieval epigraphic tradition that “makes” the epistyles of pergulae “speak” stems from the rare habit of inscribing altar screens in Early Christian times. This paper deals with written monogrammed messages engraved to order and with inscriptions engraved just before the installation of the prefabricated carved elements of some chosen examples of screens. They partly reflect the extent and variety of the messages entrusted to the altar screens, also justifying the choice of these specific supports located in the ecclesial space at the very threshold of the sanctuary.